Colonialité intérieure : le temps messianique de la traslatio imperi franquiste - Brice Chamouleau (Cahiers de Civilisation Espagnole Contemporaine)
This article offers a perspective for studying the 'internal coloniality' of Franco's regime, i.e. the uses of colonial government practices on the metropolitan populations from 1936 onwards. It discusses two main lines of interpretation, with which it agrees: the colonial ontologisation of ideological ennemies by Franco's regime and the post-colonial interpretations of the post-Franco Transition. Both of them do not take into account that Franco's regime introduces in its political rhetoric the languages of colonial self-determination in the UN and Atlanticist context. Based on the theological and legal uses of Saint Paul by Francisco de Vitoria and their return to Spain in the 1940s and 1960s, the text wishes to enlighten how coloniality returns in mainland Spain through the messianic temporalities that give shape to the « civil society » under francoism.